A Case Study of Iran Khodro Company: A Strategic Analysis - Akrad, Reza (2010)
This case study is intended to study comprehensively about the performance of Iran Khodro Corporation (IKCO), the largest automaker in the Middle East. Iran Khodro Company is the largest automobile producer in Iran. The case study has the main objectives of monitoring, evaluating and discussing Iran Khodro\'s recent and future condition in the market place based on its written case.